Contribution of nutrient diversity and food perceptions to food and nutrition security among smallholder farming households in Western Kenya: a case study - Ng'endo, Mary; Bhagwat, S.; Keding, G.B. (SAGE Publications, 2018)
Sub-Saharan Africa is the only region in the world where hunger is prevalent in over one-third of the population, with smallholder farming households, producers of over 80% of Africa’s food, facing both calorie and micronutrient deficiencies. With agricultural systems serving as the main source of all nutrients, little is known about the extent to which agricultural diversity in different seasons can meet macro- and micronutrient needs in rural Africa.Linkages between nutrient diversity and food species were investigated.A case study was conducted in Western Kenya to assess the seasonal nutrient diversity, seasonal nutrient accessibility levels, and food perceptions in 30 smallholder farms, 7 markets, and among 97 focus group discussion participants, respectively. All present food plant and animal species were inventoried and assigned to 1 of the 7 major Food and Agriculture Organization–defined food groups. Based on 2 macronutrients and 5 micronutrients, dendrogram-based nutrient functional diversity metrics were calculated.On-farm and market food species offered all 7 macro- and micronutrients under investigation, regardless of seasonal variation in species numbers. Although there were varying seasonal nutrient accessibility levels in markets, farms were especially effective in readily availing 4 of the 7 nutrients. However, the main food shortage months coincided only with maize shortage, but a diversity of local foods, deemed to be of low cultural and culinary preferences, were available.Nutrition education on the importance of a diversity of local foods in meeting dietary needs, thus stimulating the demand side, can contribute to achieving year-round household food security.